An ultra-sensitive mass spectrometer and its application to the study of uranium, thorium and lead in zircons - De Villiers, J. W. L.(Jacobus Wynand Louw) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1957.